2018
DOI: 10.1080/10749039.2018.1544645
|View full text |Cite
|
Sign up to set email alerts
|

Creating shared spaces: developing teaching through peer supervision groups

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
(31 reference statements)
0
17
0
1
Order By: Relevance
“…One study reported that cross-disciplinary CFD usually focuses more on student experience, but intradisciplinary CFD focuses more on the subject and its delivery (Hammersley-Fletcher & Orsmond, 2004; Yiend et al, 2014). Moreover, some have suggested that the primary goal of CFD is to share teaching methods and to improve opportunities for collaborative reflection on teaching, which is not bound to one discipline (de Lange & Wittek, 2018; Vian & Ashigbie, 2015). It is also acknowledged that a dominating common set of teaching values within one discipline might silence the most “radical lecturers” and reduce the variety of teaching approaches (Quinlan, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study reported that cross-disciplinary CFD usually focuses more on student experience, but intradisciplinary CFD focuses more on the subject and its delivery (Hammersley-Fletcher & Orsmond, 2004; Yiend et al, 2014). Moreover, some have suggested that the primary goal of CFD is to share teaching methods and to improve opportunities for collaborative reflection on teaching, which is not bound to one discipline (de Lange & Wittek, 2018; Vian & Ashigbie, 2015). It is also acknowledged that a dominating common set of teaching values within one discipline might silence the most “radical lecturers” and reduce the variety of teaching approaches (Quinlan, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…This might be feedback provided by a peer, specific pedagogical problems noted by a participant, teaching material that is shared with colleagues, or a teaching session observed by peers. Such cultural tools structure interaction and give purpose, for example, by describing a pedagogical problem as a starting point for further conversations or defining the roles of the involved peers during meetings (e.g., de Lange & Wittek, 2018; Kenny et al, 2014). At the same time, these mediating tools may be changed throughout CFD activities, such as when the presenting faculty refines the pedagogical problem based on input from their peers (A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Det å drøfte utfordringer i undervisningshverdagen med kolleger som man stoler på, er anbefalt som en effektiv tilnaerming for kvalitetsarbeid i høyere utdanning (Costa & Kallik, 1993;Kohut, Burnap, & Yon, 2007;Sachs & Parsell, 2013), og det anbefales gjerne å benytte en bestemt metode for å skape en forutsigbar og fokusert innramming (de Lange og Lauvås 2018;Thomas et al, 2014). Når profesjonsutøvere fra ulike miljøer møtes for å samarbeide, bidrar det til at ekspertise distribueres (Edwards 2005(Edwards , 2011de Lange & Wittek, 2018). Gjennom samarbeid må deltakerne klargjøre sin egen kompetanse, både for seg selv og andre, samtidig som det skapes ny kompetanse på tvers av de som deltar (Hontvedt, Silseth & Wittek, 2019).…”
Section: Tidligere Forskning Om Kollegaveiledningunclassified